Strategi Fundraising dalam Meningkatkan Perolehan Dana Zakat di LAZ YDSF Surabaya - Masruroh; Maryam Bte Badrul Munir (Universitas Negeri Surabaya, 2024)
Fundraising strategies have an important role in increasing the acquisition of zakat funds, but zakat management institutions in implementing fundraising strategies are less than optimal so that seen from the amount of realization of zakat fund collection in Indonesia has a large gap with the potential. This research aims to explain the fundraising strategy at YDSF Surabaya in increasing the acquisition of zakat funds and explaining the obstacles faced by YDSF Surabaya in conducting fundraising activities. The method used is qualitative with a case study approach. Researchers used data collection techniques from interviews using purposive sampling techniques, observation, and also documentation. The result showed that YDSF Surabaya in conducting fundraising strategies used two methods, namely direct fundraising and indirect fundraising conducted offline and online. The obstacles faced are not all fundraising officers master the product, the difficulty of obtaining donor numbers, the less optimal collection throgh institution’s application, the disconection of functions between divisions, limited human resouces and the emergence of similar programs in other amil zakat institutions. By using fundraising strategies, YDSF Surabaya can increase the aquisition of zakat fund every year.